A collagen hydrogel loaded with HDAC7-derived peptide promotes the regeneration of infarcted myocardium with functional improvement in a rodent model. (1st March 2019) - Zhang, Yue; Zhu, Dashuai; Wei, Yongzhen; Wu, Yifan; Cui, Weilong; Liuqin, Lingfei; Fan, Guanwei; Yang, Qiang; Wang, Zhexiang; Xu, Zhelong; Kong, Deling; Zeng, Lingfang; et al.
Graphical abstract: Abstract: Myocardial infarction (MI) leads to the loss of cardiomyocytes, left ventricle (LV) dilation, and cardiac dysfunction, eventually developing into heart failure. Most of the strategies for MI therapy require biomaterials that can support tissue regeneration. In this study, we hypothesized that the extracellular matrix (ECM)-derived collagen I hydrogel loaded with histone deacetylase 7 (HDAC7)-derived-phosphorylated 7-amino-acid peptide (7Ap) could restrain LV remodeling and improve cardiac function after MI. An MI model was established by ligation of the left anterior descending coronary artery (LAD) of C57/B6 mice. The 7Ap-loaded collagen I hydrogel was intramyocardially injected to the infarcted region of the LV wall of the heart. After local delivery, the 7Ap-collagen increased neo-microvessel formation, enhanced stem cell antigen-1 positive (Sca-1 + ) stem cell recruitment and differentiation, decreased cellular apoptosis, and promoted cardiomyocyte cycle progression. Furthermore, the 7Ap-collagen restricted the fibrosis of the LV wall, reduced the infarct wall thinning, and improved cardiac performance significantly at 2 weeks post-MI. These results highlight the promising implication of 7Ap-collagen as a novel candidate for MI therapy. Statement of Significance: The mammalian myocardium has a limited regenerative capability following myocardial infarction (MI). MI leads to extensive loss of cardiomyocytes, thus culminating in adverse cardiac remodeling and congestive heart failure. In situ tissue regeneration through endogenous cell mobilization has great potential for tissue regeneration. A 7-amino-acid-peptide (7A) domain encoded by a short open-reading frame (sORF) of the HDAC7 gene. The phosphorylated from of 7A (7Ap) has been reported to promote in situ tissue repair via the mobilization and recruitment of endogenous stem cell antigen-1 positive (Sca-l + ) stem cells. In this study, 7Ap was shown to improve H9C2 cell survival, in vitro . In vivo investigations in a mouse MI model demonstrated that intra-myocardial delivery of 7Ap-loaded collagen hydrogel promoted neovascularization, stimulated Sca-l + stem cell recruitment and differentiation, reduced cardiomyocyte apoptosis and promoted cell cycle progression. As a result, treated infarcted hearts had increased wall thickness, had improved heart function and exhibited attenuation of adverse cardiac remodeling, observed for up to 2 weeks. Overall, these results highlighted the positive impact of implanting 7Ap-collagen as a novel constituent for MI repair.